2018
DOI: 10.1021/acs.estlett.8b00507
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk and Mechanism of Microcystin Induction by Chiral Metalaxyl

Abstract: Pesticide-induced oxidative stress has been widely observed in aquatic algae. The production of microcystin caused by Microcystis aeruginosa intensified under the oxidative stress induced by solar radiation during an algal bloom. However, whether oxidative stress caused by the pollutants also contributed to toxic microcystin generation and the potential mechanism remain unknown, especially for chiral environmental contaminants. Metalaxyl, a high-volume chiral fungicide, was selected as the model to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our results revealed that R-metalaxyl treatment induced significant oxidative damage in both A. laxa and N. muscorum. In agreement, Wang et al (2018) reported that R-metalaxyl enantioselectively induced oxidative stress in the cyanobacterium M. aeruginosa. Metalaxyl stress induced a cell damage e.g., lipid peroxidation and DNA damage that was mainly mediated through ROS generation (de Sousa et al, 2013(de Sousa et al, , 2017.…”
Section: R-metalaxyl Induced Cellular Oxidative Damage and Modulated ...supporting
confidence: 71%
See 1 more Smart Citation
“…Our results revealed that R-metalaxyl treatment induced significant oxidative damage in both A. laxa and N. muscorum. In agreement, Wang et al (2018) reported that R-metalaxyl enantioselectively induced oxidative stress in the cyanobacterium M. aeruginosa. Metalaxyl stress induced a cell damage e.g., lipid peroxidation and DNA damage that was mainly mediated through ROS generation (de Sousa et al, 2013(de Sousa et al, , 2017.…”
Section: R-metalaxyl Induced Cellular Oxidative Damage and Modulated ...supporting
confidence: 71%
“…Metalaxyl toxicity inhibited mitotic cell division by impairing the biosynthesis of RNA (Fisher and Hayes, 1982). It also inhibited the nitrogen fixation (Monkiedje et al, 2002) and the photosynthetic reactions (de Sousa et al, 2017) and induced oxidative stress in M. aeruginosa (Wang et al, 2018). On the other hand, higher plants could mitigate metalaxyl induced-oxidative damage by increasing their cellular antioxidant defenses (Teixeira et al, 2011;de Sousa et al, 2013de Sousa et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…1 While pesticides remain a crucial component in the arsenal against these diseases in modern farming practices, their indiscriminate and prolonged use has given rise to two signicant challenges. [2][3][4] Firstly, it has led to the rapid development of resistance among pathogens, rendering many pesticides less effective. Secondly, the environmental pollution caused by these chemicals has become a cause for serious concern.…”
Section: Introductionmentioning
confidence: 99%
“…After invading rice plants, Xoo multiplies rapidly and disperses to the xylem vessels, causing symptoms of blight disease on rice leaves . These susceptible crops generally show up to 80% reduction in yield in severe cases. , Although chemical control has substantially contributed in alleviating diseases caused by plant pathogens, the long-term use of traditional agrochemicals (bismerthiazol [BT] and thiodiazole copper [TC]) has led to the predicament of resistance and aggravated environmental pollution because of the increasing dosages required for ensuring control efficiency. , For example, bismerthiazol has been observed to have less inhibitory activity than before against Xoo due to the emergence of BT-resistant strains. These problems highlight the need to identify green pesticides bearing broad-spectrum antibacterial activity and novel action mechanisms to manage these plant bacterial diseases.…”
Section: Introductionmentioning
confidence: 99%